PENGUJIAN SUBSTANSI PERDA DALAM SIDANG PENGADILAN PERKARA KORUPSI - Hari Purwadi (Komisi Yudisial RI, 2010)
ABSTRACTCombating corruption is also characterized by one unique decision in the District Court of Surakarta, particularly associated with the element against the law as stipulated in Article 2 paragraph (1) UUPTPK. Judges examine the material of the regulations, although not in the sense of Judicial Review, which is the authority of the Supreme Court. Material regulations testing were intended to bear out that the acts of the defendant was a nature against the law formally or deemed to be contradictive to the positive law. This study was primarily intended to explain the teachings of nature against the law, which is used by judges in legal considerations. In that context, the judges resolve a violation of Article 2 paragraph (1) Corruption Eridiction Act (UUPTPK), therefore it is different from the demands of the public prosecutor, who claimed that the defendants did not violate that article.Keywords: corruption, nature against the law, local regulations. ABSTRAKPemberantasan korupsi menjadi karakteristik yang unik dalam putusan Pengadilan Negeri Surakarta, khususnya terkait dengan unsur-unsur melawan hukum sebagaimana tertuang dalam pasal 2 paragraf (1) UUPTPK dalam konteks kewenangan hakim pidana untuk menguji kesesuaian atau ketidaksesuaian suatu peraturan daerah terhadap undang-undang. Hakim telah memeriksa materi undang-undang meskipun tidak menyingung materi dalam judicial review yang merupakan kewenangan Mahkamah Agung. Materi undang-undang menguatkan kejahatan terdakwa dengan dakwaan sifat melawan hukum sesungguhnya kontradiktif dengan hukum positif. Dalam kajian ini, hakim dalam pertimbangan hukumnya menentukan adanya perbuatan melawan hukum dari para terdakwa. Dan, menetapkan pelanggaran Pasal 2 paragraph UUPTPK, meski terdapat perbedaan sebagaimana permintaan jaksa penuntut umum yang mengklaim terdakwa tidak melanggar pasal iniKata kunci: korupsi, sifat melawan hukum, peraturan daerah